TREN ORANGTUA MENYEKOLAHKAN ANAK USIA DINI: STUDI FENOMENOLOGI - Umah, Restu Yulia Hidayatul (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This study aims to describe the background and experience of parents, as well as perform a typology on the views of parents in sending their children to school at an early age. Lately, there has been a lot of discussion about the pros and cons of enrolling early childhood children into PAUD (KB) level schools. Pro parents argue that at school, children can socialize with their friends, can learn by playing, can be independent, and much more. This research is a qualitative research with a phenomenological approach. The results of this study indicate that parents who send their children to school at an early age are motivated by the fact that children do not have friends, for the sake of children's independence, lack of educational games at home, children's desires, for children's growth and development, basic Islamic education, and reasons for adequate school facilities. Then, the experience felt by parents in sending their children to school at an early age is the number of positive changes in children. While the view of parents in sending their children to school at an early age is the need for optimizing children's growth and development; school preparation in the next stage; educational playground; and familiarity with the rules.